La tutela penale del sentimento religioso dopo la novella: il “caso Oliviero Toscani” (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. Brevi cenni all’impianto del Codice Rocco - 3. La novella del 2006 e la tutela delle confessioni religiose - 4. La giurisprudenza successiva alla novella: il caso Oliviero Toscani.The protection of religious confessions under current criminal law: the Oliviero Toscani caseABSTRACT: By the law n 85/2006 the Italian legislator modified criminal law provisions intended to protect collective religious feelings (art 402-406 criminal law code). In particular the new law has not confirmed old art 402 of the criminal law code, which provided for the generic crime of blasphemy. Insofar as the latter crime was characterised for its broad definition and scope, it raised serious questions of consistency with Art 21 of the Italian Constitution. However, the modifications introduced with law 85/2006 have been interpreted so leniently in subsequent case law that the old art 402 has been re-introduced as a matter of fact.